(untitled) (Research, Society and Development, 2021)
Introduction: Cardiovascular diseases are the main cause of morbidity and mortality in Brazil, which directly impacts hospitalizations and, consequently, infections associated with health care. Objective: to map the available evidence on the characteristics of surgical site infections in cardiac procedures performed in Brazil. Method: this review will consider studies that include people from all age groups who underwent cardiac surgical procedures in Brazil and were diagnosed with surgical site infection (SSI), whether superficial incisional, deep incisional or organ or cavity. A three-step search strategy will be used for this review. Databases to be searched include, PubMed, CINAHL, LILACS, Scielo/BDENF, Scopus, Embase, Web of Sciense. Quantitative and qualitative studies published in English, Spanish and Portuguese will be considered, with no date limit. The extracted data will be presented in diagram or tabular form, accompanied by a narrative summary. Final considerations: studies conducted in a high-income country show that there are no specific protocols or standards of care for the prevention of SSI in cardiac surgery, thus, characterizing surgical site infections involving cardiac procedures in Brazil can be useful for development prevention strategies and programs.